Wartime Teachers: Stories from the Front - Rachel K Turner; Eliel Hinojosa Jr. (Educational Considerations, 2020)
In the early 1990s, Dr. O.L. Davis of the University of Texas at Austin sought evacuee teacher and student recollections in England during World War II. The overarching purpose for Davis was to gain an understanding of the effect on schooling and education, specifically as it relates to the curriculum for students. This article continues where he left off and places focus on teacher evacuees. Of the several hundred responses from student evacuees, we utilized ten of the thirty teacher evacuees who responded to Dr. Davis. The purpose in this research endeavor seeks to discover the impact evacuations in England had on teacher evacuee curricular experiences between August of 1939 and May of 1945. Through these stories we discovered how learners, impacted by scarce materials and continuous interruptions to their daily lives, still provided support to the war effort by collecting materials and supplies. Teachers, with numerous duties and large classes, pushed themselves to find learning opportunities for their students on family farms, local ponds, and inside shelters. While traditional subject matter activities were not always possible, teachers utilized what was around them in an effort to build educational experiences like plays, projects, and current event studies. Constant interruption, building changes, and billeting issues made the context in which these teachers found themselves less than ideal. Yet they made the most of their time for the sake of their students’ learning.
Keywords: History; Culture; England; World War II; Evacuee; Teacher; Schwab